Faktor Risiko Kejadian Ulkus Diabetik Pada Penderita Diabetes Mellitus Tipe 2 di RSUD Kabupaten Muna - Arimaswati Arimaswati; Nina Indriyani Nasruddin; Agussalim Ali; Tien Tien; Pranita Aritrina; Adellya Febriyani Hadini; Adry Leonardy Tendean (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Diabetes mellitus (DM) is a non-communicable disease that has become a serious public health problem. Diabetic ulcers are a form of chronic complications of type 2 diabetes that often occur. Facto factors that influence the incidence of diabetic ulcers in people with type 2 diabetes are direct factors including age, gender, education, occupation, long suffering from diabetes, smoking, sports, use of footwear and irregular foot care. Meanwhile, indirect factors are family support in the form of emotional support, appreciation support, instrumental support, and alternative support. The purpose of this study was to determine the risk factors associated with the incidence of diabetic ulcers in type 2 diabetes mellitus sufferers at RSUD Kabupaten Muna. This research is a type of observational analytic using aapproach case control study. The case group was diabetic ulcer patients diagnosed by a doctor and recorded in the medical record, the control group was type 2 diabetes mellitus patients diagnosed by a doctor and recorded in the medical record. The number of samples was 66 samples consisting of 33 case groups and 33 control groups. The sampling technique usedmethod purposive sampling. The results of research at RSUD Kabupaten Muna showed the results of bivariate analysis of age showed values ​​(OR: 11,200; CI 95%; 3,388-37,020), duration of DM ≥ 10 years showed a value (OR: 8,543; CI95%; 2,796-26,104) OR: 10,075; 95% CI; 2,052-49,469), hypertension showed a value (OR: 6,250; CI 95%; 2,131-18,330), GDS levels showed a value (OR: 9,000; CI95%; 2,870-28,224), sport showed a value ( OR: 14,062; 95% CI; 4,278-46,230), smoking showed a value (OR: 13,796; 95% CI; 4,238-44,910). Age, duration of diabetes mellitus ≥ 10 years, obesity, hypertension, GDS levels, sport, and smoking are risk factors associated with the incidence of diabetic ulcers in type 2 diabetes mellitus sufferers at RSUD Kabupaten Muna.